2017
DOI: 10.1121/1.4988421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical rainbow trapping and Bloch oscillations in chirped metallic beams

Abstract: The mechanical rainbow trapping effect and the mechanical Bloch oscillations for torsional waves propagating in chirped mechanical structures are here experimentally demonstrated. After extensive simulations, three quasi-one-dimensional chirped structures were designed, constructed and experimentally characterized by Doppler spectroscopy. When the chirp intensity vanishes, a perfect periodic system, with bands and gaps, is obtained. The mechanical rainbow trapping effect is experimentally characterized for sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This concept has been developed for acoustics, 7 ultrasonics 8 and structural vibration. 9,10 Moreover, Meng et al. 11 have shown that optimal spatial distribution of the tuning frequency of each resonator can be further explored for different performance criteria in multi-frequency metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been developed for acoustics, 7 ultrasonics 8 and structural vibration. 9,10 Moreover, Meng et al. 11 have shown that optimal spatial distribution of the tuning frequency of each resonator can be further explored for different performance criteria in multi-frequency metamaterials.…”
Section: Introductionmentioning
confidence: 99%